Acute effects of 2 consecutive simulated badminton matches on the shoulder range of motion and isometric strength of elite youth players - Fernandez-Fernandez, J.; Lopez-Valenciano, A.; Garcia-Tormo, J. V.; Cabello-Manrique, D.; García-López, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To analyze the influence of playing 2 consecutive prolonged badminton matches on the shoulder strength and range of motion (ROM) of young players.